As reproduções de obras de Antonio Canova e Bertel Thorvaldsen em gesso patinado e terracota do Museu Nacional Soares dos Reis - Morais, Rui (2017)
One of the most interesting aspects of 18th century glyptography is the use of motifs from ancient and contemporary sculpture in the gurative repertoire of gem engravers. At the height of their expansion, from the mid-1700s, the most imitated motifs (apart from the clients portraits) came from coins and famous gems of Antiquity, even though the engravers would at times give themselves to whimsical reinvention. Some of these depictions were mentioned in the work of Winckelmann, but the majority copied pieces found in excavations at Pompeii and Herculaneum. At the end of the 18th century, particularly from 1790, gem engravers began to imitate the already famous sculptures of Antonio Canova (1757-1822) and, later, of Bertel orvaldsen (1770-1844), as well as of some of their students and followers, such as, Gibson, Wol, Trentanove, Bienaimé, Tenerani